Improved Adhesion of Bacterial Cellulose on Plasma-Treated Cotton Fabric for Development of All-Cellulose Biocomposites - Linda Ogrizek; Janja Lamovšek; Gregor Primc; Mirjam Leskovšek; Alenka Vesel; Miran Mozetič; Marija Gorjanc (Molecules)
Cellulose produced by bacteria (BC) is considered a promising material for the textile industry, but the fragile and sensitive nature of BC membranes limits their broad applicability. Production of all-cellulose biocomposites, in which the BC is cultivated in situ on a cotton fabric, could solve this problem, but here a new issue arises, namely poor adhesion. To overcome this challenge, cotton fabric was modified with low-pressure oxygen plasma in either afterglow, E-mode, or H-mode. All-cellulose biocomposites were prepared in situ by placing the samples of cotton fabric in BC culture medium and incubating for 7 days to allow BC microfibril networks to form on the fabric. Modification of cotton fabric with oxygen plasma afterglow led to additional functionalization with polar groups, and modification with oxygen plasma in H-mode led also to etching and surface roughening of the cotton fibers, which improved the adhesion within the biocomposite. In addition, these biocomposites showed higher deformation capacities. Modification of the cotton fabric over a longer period in E-mode was found to be unsuitable, as this caused strong etching, which led to the defibrillation of cotton fibers and poor adhesion of BC. This study highlights the potential of low-pressure plasma treatment as an environmentally friendly method to improve the performance of cellulose-based biocomposites.